The economics of James Steuart - Tortajada, Ramon (Routledge studies in the history of economics ;, 1999)
Addressing all aspects of Steuart's contribution to economics this book reveals the particular importance of his work on monetary issues and highlights ways in which he prepared the ground for a new conception of economic relations.